(untitled) (Dhaka University Journal of Biological Sciences, 2015)
Biochar and biomass were applied at the rate of 5 t/ha to soils that received arsenic containing water at a rate of 1 mg/l arsenic (80% arsenite and 20% arsenate). After 36 days of growth of Kalmi plants, the yield parameters, such as arsenic accumulation and fate of arsenic vis‐á‐vis biochar addition had been examined. The results showed that the addition of biochar had a positive but non‐significant impact on the yield parameters. Addition of biochar in the soil insignificantly increased the number of plants and the uptake of arsenic while the concentrations of extractable arsenic in soil decreased with biochar treatments. Source of biochar has a role to play towards this direction. Dhaka Univ. J. Biol. Sci. 24(2): 111-119, 2015 (July)